Propanol and its blend in diesel engines: An extensive review - Celebi, Yahya; Cengiz, Mazlum; Aydin, Hueseyin (Elsevier Sci Ltd, 2025)
Renewable energy resources offer remarkable solutions to energy-related issues of reserve depletion and the emissions of harmful substances caused by fossil fuels. Energy demand increases as the world population grows. To fulfill the worldwide growing energy demand, especially in the transportation sector, biofuels are viable candidates to be used as partial or fully in diesel engines within existing engine infrastructure thanks to their abundant feedstocks and low costs. Propanol is one promising fuel for diesel engines. It can be produced from both petrochemical and biochemical routes which make it feasible to produce on large-scale. Moreover, it has higher energy content and boiling point, and lower hygroscopicity in comparison with lower alcohols. This review study explores comprehensive utilization of propanol and its blends in diesel engines to show its impacts on combustion behaviors, performance metrics and exhaust emissions. Furthermore, the paper comprehensively analyzes the production techniques, supply and demand trends, sustainability and safety considerations and other fuel applications of propanol. The paper concludes by highlighting key findings and identifying areas for further research. Overall, this review offers crucial insights into the potential of propanol to decrease the dependence on fossil diesel fuel and improve engine performance and its associated emissions.
Keywords: Propanol; Diesel engine; Biofuel; Alcohol; Emissions; Combustion performance